In vitro anti-fungal and anti-bacterial activity of Drymoglossum piloselloides L. Presl. against several fungi responsible for Athlete's foot and common pathogenic bacteria - Somchit, Muhammad Nazrul; Hassan, H.; Ahmad, Zuraini; Chong, L. C.; Mohamed, Zeehaida; Zakaria, Zainul Amiruddin (Academic Journals, 2011)
Drymoglossum piloselloides (DP) is a small epiphytic fern commonly seen on trunks of older trees. The antimicrobial activity of water, ethanol and chloroform extracts of DP was tested against Trichophyton rubrum ATCC 40051 and Trichophyton mentagrophytesATCC 40004 which are the two most commonly cause of Athlete’s foot, Candida albicansATCC 14053, Candida tropicalis ATCC 14056, Microsporum canis (clinical isolate) andAspergillus fumigatus ATCC 14109. The chloroform and ethanol extracts only had mild activity against the Trichophyton spp. and the water extract was devoid of any activity. The anti-fungal activity was statistically less potent than griseofulvin and fluconazole or itraconazole. The anti-bacterial activity of DP extracts was also tested against four bacterial strains using the disc diffusion and microdilution methods. Escherichia coliATCC 25922, Staphylococcus aureus ATCC 25923, Streptococcus pneumoniae ATCC 49619, Bacillus subtilis and Salmonella enteritidis (clinical isolates). The antibacterial activity against gram positive bacteria was detected only in water extract minimum inhibitory concentration (MIC) 12.5 mg/ml against S. aureus. The minimum bactericidal concentrations of 25 mg/ml against S. aureus. This antimicrobial activity was compared to standard antibiotics (ampicillin and chloramphenicol). The water extract had statistically less potent anti-bacterial activity when compared to ampicillin and chloramphenicol. The anti-fungal and anti-bacterial activity of DP was minimal this may be due to the testing of crude extracts. Future studies of purified or semi purified samples may produce better results and may potentially be used in the treatment of Athlete’s foot and the related secondary bacterial infections.